Converting to Intubation During Non-intubated Thoracic Surgery: Incidence, Indication, Technique, and Prevention - Chiang, Xu-Heng; Lin, Mong-Wei (Frontiers in Surgery, 2021)
Traditionally, intubated general anesthesia with one-lung ventilation is standard in thoracoscopic surgery. However, in recent decades, non-intubated thoracoscopic surgery (NITS) has become an alternative method to minimize the adverse effects of intubated general anesthesia. Non-intubated procedures result in fewer adverse events than tracheal intubation and general anesthesia, such as intubation-related airway injury, ventilation-induced lung injury, prolonged hospital stay, and postoperative nausea and vomiting. Despite these benefits, surgeons must consider the possibility of converting to intubation during NITS as the conversion rate is between 2% and 11%, varying between regions and learning time. The conversion rate is also affected by race, body size, the learning curve, and the surgical team’s preferred methods. There are surgical (e.g., significant respiratory movements, uncontrolled bleeding, hindered surgical fields, large tumor sizes, adhesions) and anesthetic (e.g., hypoxemia, hypercapnia, airway spasms) reasons for converting to intubation. When a conversion is deemed necessary by the surgical team, the members should be well-prepared and act rapidly. Anesthesiologists should also feel comfortable intubating patients in the lateral decubitus position with or without bronchoscopic guidance. Patient selection is the key factor for avoiding conversion into an intubated surgery. Patients with an American Society of Anesthesiologists grade 2 or less, a body mass index <25, and less surgical complexity may be good candidates for NITS. Careful monitoring, adequate anesthesia depth, an experienced surgical team, and sufficient preparation can also prevent conversion. Conversion from a non-intubated into intubated thoracic surgery is unwanted but not inevitable. Therefore, NITS can be successful when performed on select patients by a well-prepared and experienced surgical team and is worthy of recommendation owing to its non-invasiveness.